Acceptability and response to a postal survey using self-taken samples for HPV vaccine impact monitoring. Issue 7 (11th October 2011) - Sinka, Katy; Lacey, Michelle; Robertson, Chris; Kavanagh, Kim; Cuschieri, Kate; Nicholson, Donna; Donaghy, Martin
Abstract : Objective: To assess the feasibility and acceptance of a postal survey to measure human papillomavirus (HPV) prevalence and monitor vaccine impact, using self-taken specimens from young women who do not attend their first cervical screening appointment. Methods: Focus groups informed the survey design identifying factors that would influence acceptability. Postal testing kits were sent to a nationally representative sample of unscreened women. Overall response rate, the influence of different specimen types (urine or vaginal swab) and the receipt of a reminder letter on participation were calculated. Specimens were tested anonymously for HPV. Individual test results were not provided. Results: Of 5500 kits sent, 725 were returned (13.2%). Fifty-two women actively opted out. There was a higher return rate for urine kits (13.7% vs 12%) and from those who received a reminder letter (15.5% vs 12.2%). Response was influenced by deprivation (10.3% in the most deprived quintile vs 16.2% in the least). Overall weighted HPV prevalence was 35.9% (40.0% from swab specimens and 31.9% from urine). Conclusions: Some women were willing to participate in anonymised postal testing. However, the low uptake means that HPV prevalence results are difficult to interpret for ongoing surveillance. Monitoring HPV vaccine impact outwith the cervical screening programme remains challenging.